Valvular disease in patients requiring long-term left ventricular assist devices: pathophysiology and therapeutic options. (February 2012) - Firstenberg, Michael S; Sai-Sudhakar, Chittoor B; Anyanwu, Anelechi
It is becoming clear that valvular pathology in patients requiring long-term mechanical ventricular support is an evolving, poorly understood and potentially dynamic problem. While strict guidelines are lacking, there is a growing experience in the understanding and management of the growing spectrum of valvular problems in this complex patient population. While the management of tricuspid and aortic regurgitation is of significant concern and may potentially have significant adverse impact on outcomes, other valvular pathologies can be problematic and require management in a manner unique to each patient.